(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
present scenario of climate change on agriculture in the form of groundwater depletion, flood, salinity, several new borne species of pathogens, and insect-pests, brings serious attention to developing ice varities with higher resilience. As most of the above-ground plant parts are already explored to combat these situations, now the time came to improve the yield by reshaping the below-ground plant parts. Designing the root system architecture (RSA) in rice is one of the most imperative traits for such conditions, as modification in the root architecture in rice will be the best strategy to improve water uptake and nutrient acquisition. Many quantitative trait loci (QTLs) and genes playing the role for RSA have been recognized to improve the root parameters and the confirmed QTLs can be introgressed through marker-assisted backcross breeding to develop ideal genotypes. The recent advances in molecular plant breeding including genome editing, mutation study and genetic engineering has shown their potency in this direction. Even though most of the root architectural traits in rice are not document properly, the present review will make comfortable to the future researchers on the aspects of molecular mechansms involved in root traits development viz., genes functioning for root traits, their development, physiological role for moisture, and mineral-nutrient uptake under stressful environment.